The concept of Existentialism in Prostitution Literature of Thai Writers - Chaisanit, Siripen; Suwaddhanavisutdhisaragun, Phrakhrupalad (Journal of Dhamma for Life, 2025)
This research aims to 1) study the concept of existentialism, 2) study the literature of prostitutes by Thai writers, 3) analyze the concept of existentialism in the literature of prostitutes by Thai writers, and 4) critique the concept of existentialism in the literature of prostitutes by Thai writers. This is a documentary study focusing on the concept of existentialism in the literature of prostitutes by Thai writers. The research results found that 1. Sartre's existentialism gives great importance to freedom. He said that man is freedom. The human condition and freedom are inseparable. Man is the one who determines his own destiny. Therefore, each person's life does not depend on the inspiration of any gods or prophets. No supernatural being can determine his destiny. The meaning of a person's life depends on the decision and action of that person. 2. The literature of prostitutes by Thai writers shows the literary excellence of the author. A total of 3 works of prostitutes from 3 writers: Ying Kon Chuea by K. Surangkhanang, Sanimsroi by Rong Wong Sawang, and Lueam Salap Lai by Kritsana Asoksin. 3. Analyze the concept of existentialism in literature, linking it to Sartre's philosophy of state and emptiness, freedom and responsibility, love and sexual relationships, and suffering. 4. Criticize the concept of existentialism in literature. The story of prostitutes in society is still in a state of neither swallowing nor spitting out, whether to accept the legitimacy of the existence of prostitutes, even if it is said in terms of philosophical freedom.